Estimation of Caffeine and Sugar in Some Selected Brands of Energy Drinks Available in Libyan Markets - Wafa Khalleefah Amhimmid; Suad Ali Uneis; Sara Sharef Altabeeb; Nader Abdulhamid Elaziby (المجلة الأفروآسيوية للبحث العلمي, 2024)
Energy drinks are very popular worldwide, especially among teenagers and young adults. The increased consumption of energy drinks raises serious health concerns due to the high content of sugar, caffeine, and other ingredients. This study aims to determine the amount of caffeine and sugar present in some energy drinks available in Libyan markets, and its potential health effects.7 different brands of energy drinks were purchased from random markets in Tripoli. Caffeine was extracted from each drink and analyzed by UV-VIS Spectrophotometric method. Reduced sugar, pH, NaCl, CO2, Ascorbic acid, and citric acid also were analyzed. the pH values were highly acidic ranging from 1.20 – 2.18, and NaCl% ranged from 0.146% to 0.641% which exceeded the Libyan standard limitation, also CO2 content was exceeded in most of the samples ranging between 3.46 to 10.16 (g/cm3). as for the reducing sugar content ranged from 5.5 – 31.11 mg/100ml. The results showed that the caffeine content of the studied drinks ranged from 9.71 to 41.29 ppm. The caffeine concentration in all drink samples analyzed in this study was within the allowable limits established by the FDA